2016
DOI: 10.1080/17446651.2016.1220298
|View full text |Cite
|
Sign up to set email alerts
|

Healthy obesity as an intermediate state of risk: a critical review

Abstract: Introduction: Obesity is a top public health priority but interventions to reverse the condition have had limited success. About 1-in-3 obese adults are free of metabolic risk factor clustering and are considered 'healthy', and much attention has focused on the implications of this state for obesity management. Areas covered:We searched for individual studies, systematic reviews, and meta-analyses which examined correlates and outcomes of metabolically healthy obesity. We discuss the key roles of fat distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 111 publications
0
8
0
1
Order By: Relevance
“…Approaches which meet this definition include Intuitive Eating (IE), those informed by the Health at Every Size (HAES) principles, and weight‐inclusive, non‐diet approaches . These approaches were initially regarded as problematic by some, with the core dispute being about the existence of ‘healthy obesity’ . More recently acceptance for them has grown due to mounting evidence of the improvements in morbidity, mortality and quality of life of lifestyle behaviours regardless of BMI and poor likelihood of long‐term maintenance of behavioural weight losses .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approaches which meet this definition include Intuitive Eating (IE), those informed by the Health at Every Size (HAES) principles, and weight‐inclusive, non‐diet approaches . These approaches were initially regarded as problematic by some, with the core dispute being about the existence of ‘healthy obesity’ . More recently acceptance for them has grown due to mounting evidence of the improvements in morbidity, mortality and quality of life of lifestyle behaviours regardless of BMI and poor likelihood of long‐term maintenance of behavioural weight losses .…”
Section: Introductionmentioning
confidence: 99%
“…8,9,14 These approaches were initially regarded as problematic by some, 15 with the core dispute being about the existence of 'healthy obesity'. 16 More recently acceptance for them has grown due to mounting evidence of the improvements in morbidity, mortality and quality of life of lifestyle behaviours regardless of BMI 17,18 and poor likelihood of long-term maintenance of behavioural weight losses. 18,19 Weight bias and stigma driven by a cultural and medical 'thin ideal' have also received research attention for their negative effects on health outcomes and widespread occurrence in society and healthcare settings, 20 problems that WN approaches strive to address directly.…”
Section: Introductionmentioning
confidence: 99%
“…Termed ‘metabolically healthy obesity’, population-based studies have identified an obesity phenotype that is not accompanied by a clustering of adiposity-associated cardio-metabolic risk factors ( 1 ). Although tendencies for metabolic decline and for developing type 2 diabetes are becoming clear ( 1 ), associations of healthy obesity with outcomes related to cardiovascular disease and mortality are less consistent ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Termed ‘metabolically healthy obesity’, population-based studies have identified an obesity phenotype that is not accompanied by a clustering of adiposity-associated cardio-metabolic risk factors ( 1 ). Although tendencies for metabolic decline and for developing type 2 diabetes are becoming clear ( 1 ), associations of healthy obesity with outcomes related to cardiovascular disease and mortality are less consistent ( 2 , 3 ). One explanation for these inconsistencies may be differences in the duration of follow-up used across studies, with those using shorter follow-up times tending to find no association between healthy obesity and outcomes ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Um estudo acompanhou enfermeiras durante 16 anos nos EUA e constatou que o risco de elas desenvolverem diabetes cresceu gradativamente com IMC entre 22 e 35 kg/m 2 . Com IMC menor do que 25 associados a fatores de vida saudável como manter uma boa alimentação e praticar exercício físico diminui o risco de desenvolver diabetes tipo 2 em 90%24 .…”
unclassified